Analisis Perkembangan Teknik Sulaman Tangan - Butar-Butar, Khairunnisa; Hasibuan, Elfi Husnita; Meilasari, Retno Desti Dwi (Universitas Negeri Gorontalo, 2025)
Decorating fabric is an art of creating creations on materials in the form of fabric using ornamental motifs so that the fabric looks beautiful. The technique of decorating fabrics has been known by ancestors since time immemorial. The hand embroidery technique consists of several basic techniques that can be applied as decoration to form a pattern or motif. Some basic punctures on hand embroidery such as jelujur skewers, feston skewers, chain stitches, trace stabs, chain stitches, cross-stitches / Stars, and flannel (herringbone) skewers. The author uses a qualitative type of research. This form of research is literature analysis, namely by looking for references or data. The components of analysis are data reduction, presenting data and drawing conclusions or verification. In the study, two types of analysis were carried out, namely 1) analysis of the type / name of embroidery, visual appearance and description of embroidery techniques. Then the next analysis 2) identifies the types of embroidery techniques that exist based on the development of the basic types of hand embroidery stitching techniques. In its development, this embroidery technique is the application of one or more of the basic punctures of hand embroidery with other additions both materials and complementary techniques. Finally, it can be concluded that the embroidery technique is an expoloration process on the types of basic punctures, the use of materials to the techniques used such as pulling thread and scissoring. In other words, it does not rule out the possibility of recreating hand embroidery techniques without any restrictions.